Does active portfolio management create value? An evaluation of fund managers' decisions - Stefan Engström (Stockholm School of Economics, The Economic Research Institute (EFI), 2004)
In this paper, I obtain new measures of the value of active portfolio management by forming replicating portfolios. These measures allow for a separate evaluation of fund managers' strategic and tactical decisions. I also obtain new evidence on the value of trading by decomposing it into long-term trading decisions, short-term trading decisions, and trading that is the result of regulatory restrictions. Overall, the evidence supports the value of active portfolio management and that the average fund manager creates value for its investors. Moreover, the results show a positive relation between the value created and trading activity.
Keywords: G11; G12; G23; 330; Mutual Funds; Portfolio Evaluation; Performance Attribution; Trading; Portfolio-Management; Theorie